2006
DOI: 10.1007/s00595-006-3178-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Evaluation of the Cardiac Surgery Environment Accompanying Hospital Relocation

Abstract: Hospital relocation resulted in an improved operating room environment with less bacterial contamination of intraoperative salvaged blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Additionally, knowing that heart surgery is the medical specialty which consumes the most blood products ( 9 ) , the cell saver (CS) is used, a device which recovers blood losses from the surgical field and from the residual volume of the extra-body circuit to submit it to a “cleaning” process, obtaining a certain volume of red blood cells which is reinfused into the patient (re-infusion bag). In this device, bacterial growth was detected in 85% of the samples of recovered blood ( 10 ) and in the samples of red blood cells to reinfuse GRAM+ bacterial commensals ( 11 ) , and even in other surgical procedures like traumatologic ones (scoliose in Pediatrics), where the CS was also used and the same commensals were detected in the re-infusion bag, but of the staphylococcus genus ( 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, knowing that heart surgery is the medical specialty which consumes the most blood products ( 9 ) , the cell saver (CS) is used, a device which recovers blood losses from the surgical field and from the residual volume of the extra-body circuit to submit it to a “cleaning” process, obtaining a certain volume of red blood cells which is reinfused into the patient (re-infusion bag). In this device, bacterial growth was detected in 85% of the samples of recovered blood ( 10 ) and in the samples of red blood cells to reinfuse GRAM+ bacterial commensals ( 11 ) , and even in other surgical procedures like traumatologic ones (scoliose in Pediatrics), where the CS was also used and the same commensals were detected in the re-infusion bag, but of the staphylococcus genus ( 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Ishida et al [6] reported that airborne bacteria in the hospital environment have been a major source of post-operative 7) in the bacteria population of the different sampling time whereas it was not so for fungi population (氈 2 = 0.285 7). Male medical ward (MMW) and male surgical general (MSG) recorded the highest bacterial and fungal growth while the operating theatre (OT) was almost free of microbial burden.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Awosika et al (2012) 5 reported that nosocomial infections can be contracted from contact with a carrier directly or indirectly through inanimate objects or air. Ishida et al (2006) 6 also showed that, airborne bacteria are major source of infection after operation and a serious illness in the Intensive Care Unit. In the United States, approximately 1.7 million hospital-associated infections from all types of bacteria are responsible for 99,000 deaths each year; so about 10%, or 2 million patients are being infected each year, 7,8 In France, According to Lepoutre et al (2005) 9 Heshowed that prevalence of nosocomial infection was 5.9% in 2001.…”
Section: Introductionmentioning
confidence: 99%